India - Jharkhand : Public Financial Management and Accountability Study - World Bank (Washington, DC, 2013)
Jharkhand, India's youngest and 28th state came into existence in November 2000 pursuant to the reorganization of the erstwhile State of Bihar by the Bihar State Reorganization Act, 2000. More than 77 percent of the population of the state resides in rural areas and depends on agriculture for sustenance. Jharkhand is one of the richest states in the country in terms of mineral resources. Close to half of the gross domestic product (GSDP) of the state emanates from industry which includes mining, quarrying and registered manufacturing. But the high degree of industrialization has not resulted in a high level of income for the state. While the structure of the output indicates a high level of industrialization, the structure of employment reveals the predominance of agriculture. The purpose of this study is to make an objective assessment of the Public Financial Management and Accountability (PFMA) system of the state, identify its strengths and weaknesses and areas that may be in need of reforms and related capacity building. This study is a prerequisite to determining the precise nature and extent of any capacity building initiatives in Jharkhand. The study provides the Government a diagnostic tool for establishing priorities and to develop a baseline for monitoring future PFM performance of the state.